Influence of Ocular Residual Astigmatism and Target-Induced Astigmatism on the Efficacy of the Implantation of a Toric Implantable Collamer Lens With Central Hole for Myopic Astigmatism Correction - Zhao, Jing; Zhao, Jiao; Yang, Wen; Sun, Ling; Qian, Yishan; Wang, Xiaoying; Zhou, Xingtao (Frontiers in Medicine, 2022)
Purpose: To investigate the effects of ocular residual astigmatism (ORA) and target-induced astigmatism (TIA) on the efficacy of Toric implantable collamer lens (TICL) with central hole for myopic astigmatism correction. Methods: Retrospective case series. One hundred and eighteen eyes implanted with a TICL (V4c) from 118 patients were included. Subjective refraction and corneal topography were examined preoperatively, at 1 and 12 months postoperatively. The eyes were divided into a low-ORA (≤0.5D) and a high-ORA (>0.5D) group based on vector analysis and into a low-TIA (≥0.75D & ＜2D) and a high-TIA (≥2D & ≤4D) group according to preoperative refractive astigmatism. Correction index (CI) and index of success (IOS) were compared between different groups. Results: All surgeries were uneventful, and no complications occurred during follow-up. At 1 and 12 months postoperatively, no significant differences were found in CI or IOS values between the high and low ORA groups, while significantly higher CI and lower IOS were detected in the high-TIA compared with the low-TIA group (P<0.05). No significant difference was found in CI between 1 month and 12 months postoperatively in either group (P >0.05). However, a significantly lower IOS was found at 12 months compared with 1 month postoperatively for each group (P <0.05). Conclusions: TICL implantation is effective in correcting myopic astigmatism and is more effective in eyes with high TIA, while ORA has a minor effect.